From natural resources and environmental accounting to construction of indicators for sustainable development - Knut H. Alfsen; Mads Greaker (Statistics Norway, Research Department, 2006)
Norway has a long history in trying to develop management tools for sustainable development. From the early development of natural resources accounts in the 1980's, through discussions of the usefulness of indices like "green GDP" to efforts of developing sustainable development indicators, experiences have been gained. The paper seeks to both describe the landscape and discussions associated with the key terms, and to communicate some lessons drawn from the Norwegian experiences. The conclusion focuses on the fact that whatever information is collected and organised to support the relevant decision-making processes, the final outcome should always be judged in terms of its impacts on policy processes. Thus, we issue a warning against large-scale development of information systems, without due regard to the final utilisation of the output.
Keywords: N5; Q2; Q3; 330; Green accounting; Natural resource and environmental accounting; sustainable development indicators; green GDP; SEEA